PENINGKATAN KREATIFITAS BELAJAR MELALUI PENGGUNAAN MODEL MAKE A MATCH DI KELAS XI IS SMAN 2 BATUSANGKAR - Eriswati, Eriswati (JESS (Journal of Education on Social Science); Vol 3 No 2 (2019): Special Edition, 2019)
This study tried to investigate whether the use of cooperative learning model of Make A Match type could increase the learning activity of students in the class XI IS of SMAN 2 Batusangkar. This research is qualitative and carried out in class XI IS of SMAN 2 Batusangkar in the academic year 2017/2018. The study was conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection. The data of the student activities was obtained from observer using observation sheet. The finding of this study indicated that Civics learning using coopertive learning models of type Make A Match could improve the student activities in civics learning at the class XI IS of SMAN 2 Batusangkar. Learning activities of the students in the second cycle had increased significantly. Based on the finding of this study, it is concluded that learning by using cooperative learning model of Make A Match type could improve the civics learning activities in the classroom XI IS of SMAN 2 Batusangkar.